S-100 immunostaining in the distinction of borderline tuberculoid leprosy from other cutaneous granulomas - Rajalakshmi Tirumalae; Anto Ignat Stany; Sharan Shanubhogue; Inchara K Yeliur (Wolters Kluwer Medknow Publications, 2014)
Background: Histopathologic diagnosis of borderline tuberculoid leprosy (BTL) is fraught with hurdles. It overlaps with other granulomas and documenting nerve involvement is the key to correct diagnosis. This is difficult on H and E sections alone. S-100 immunostaining may help in this regard. Objectives: To study the patterns of nerve involvement in BTL and other cutaneous granulomas using S-100 immunostain and compare its sensitivity with that of H and E staining, in both adequate and inadequate biopsies. Materials and Methods: A total of 20 cases of BTL were reviewed. And, 19 biopsies from other cutaneous granulomas were taken as controls. S-100 immunostaining was done on paraffin sections. The pattern of nerve involvement was graded as intact, infiltrated and/or fragmented, intact with perineural inflammation. Results: Of the 20 cases of BTL, S-100 demonstrated infiltrated and/or fragmented nerves in 15 and absent nerves in 5 cases. H and E stain identified neuritis in eight cases. The sensitivity of S-100 and H and E is 0.78 and 0.41. In the 19 controls, S-100 identified normal nerves in 16 with 7 showing perineural inflammation only and their absence in 2 cases. H and E identified normal nerves in nine cases. The sensitivity of S-100 and H and E is 0.83 and 0.41. In biopsies where subcutis was absent, the sensitivity of S-100 in identifying nerve involvement is 0.66 compared with H and E 0.33. Conclusion: S-100 staining is an efficient ancillary aid in distinguishing BTL from other granulomas and is superior to H and E in identifying nerve involvement, even where subcutis is absent. Infiltration and/or fragmentation of nerves by S-100 is the only reliable marker of BTL.